Degassing during quiescence as a trigger of magma ascent and volcanic eruptions - Girona, Társilo (2016)
Understanding the mechanisms that control the start-up of volcanic unrest is crucial to improve the forecasting of eruptions at active volcanoes. Among the most active volcanoes in the world are the so-called persistently degassing ones (e.g., Etna, Italy; Merapi, Indonesia), which emit massive amounts of gas during quiescence (several kilotonnes per day) and erupt every few months or years. The hyperactivity of these volcanoes results from frequent pressurizations of the shallow magma plumbing system, which in most cases are thought to occur by the ascent of magma from deep to shallow reservoirs. However, the driving force that causes magma ascent from depth remains unknown. Here we demonstrate that magma ascent can be triggered by the passive release of gas during quiescence, which induces the opening of pathways connecting deep and shallow magma reservoirs. This top-down mechanism for volcanic eruptions contrasts with the more common bottom-up mechanisms in which magma ascent is only driven by processes occurring at depth. A cause-effect relationship between passive degassing and magma ascent can explain the fact that repose times are typically much longer than unrest times preceding eruptions, and may account for the so frequent unrest episodes of persistently degassing volcanoes.